English Immersion U.S.A. Program (EIP) - An educational and sociocultural experience (Research, Society and Development, 2020)
The present paper shares an account of the experience of the English Immersion U.S.A Program (EIP), promoted by the U.S. Mission to Brazil as a positive response to the need to outreach to minority and disadvantaged public school students in Brazil after the selection of the Youth Ambassadors program. The account conveys the experience of the selection process, the program itself, and highlights the possibility of the program to  (1) foster international cooperation to reach the goals of the U.S. Mission to Brazil through both education and social inclusion; (2) allowed the participants to have an immersive experience in the U.S. culture and allowed them to practice and sharpen their English language skills; (3) allowed the participants to get to know Brazil itself better as they interacted with fellow Brazilians from different parts of the country; (4) make an educational environment to allow transformative learning, and (5) achieve Sustainable development goal number 17.